Application of spectroscopic and chromatographic methods for the analysis of non-halal meats in food products - Rohman, Abdul; Ahmad Fadzillah, Nurrulhidayah (Springer Nature Switzerland, 2021)
Meat is one of the major food groups which is frequently adulterated for economic reasons. In line with halal certification, the presence of non-halal meats in food products must be identified. Mislabelling and undeclaring meat types are typically seen in meat-based products such as meatballs, burgers, sausages and Salami. Therefore, the application of analytical methods for the detection, identification, and confirmation of non-halal meats is a must. This chapter highlighted the application of spectroscopic and chromatographic-based methods combined with several chemometrics for the identification and confirmation of non-halal meats in food products. Spectroscopy offered more accelerating methods with higher accuracy rates throughout the screening process for non-halal meats. Further confirmation can be done using chromatography by identifying specific markers present in analyzed non-halal meats.